Aircraft surveillance systems radar limitations and the advent of the automatic dependent surveillance broadcast - Ali, Busyairah Syd (Routledge, 2018)
This book addresses the limitations of radar to support ATC in various operational environments, identified and verified by analysing five years of safety data from Avinor, the Air Navigation Service Provider (ANSP) in Norway. It derives a set of taxonomy and from this develops a causal model for incident/accident due to limitations in the surveillance system.